Dual-targeting AAV9P1-mediated neuronal reprogramming in a mouse model of traumatic brain injury - Jingzhou Liu; Xin Xin; Jiejie Sun; Yueyue Fan; Xun Zhou; Wei Gong; Meiyan Yang; Zhiping Li; Yuli Wang; Yang Yang; Chunsheng Gao (Neural Regeneration Research, 2024)
[INLINE:1] Traumatic brain injury results in neuronal loss and glial scar formation. Replenishing neurons and eliminating the consequences of glial scar formation are essential for treating traumatic brain injury. Neuronal reprogramming is a promising strategy to convert glial scars to neural tissue. However, previous studies have reported inconsistent results. In this study, an AAV9P1 vector incorporating an astrocyte-targeting P1 peptide and glial fibrillary acidic protein promoter was used to achieve dual-targeting of astrocytes and the glial scar while minimizing off-target effects. The results demonstrate that AAV9P1 provides high selectivity of astrocytes and reactive astrocytes. Moreover, neuronal reprogramming was induced by downregulating the polypyrimidine tract-binding protein 1 gene via systemic administration of AAV9P1 in a mouse model of traumatic brain injury. In summary, this approach provides an improved gene delivery vehicle to study neuronal programming and evidence of its applications for traumatic brain injury.